All the King's Men (and Citizens): Aristotle's Kingship and the Political - Rosler, Andres Bernardo (2018)
Riesbeck does not claim that his account of the political in Aristotle delivers a demonstrative blow that no one can resist should they happen to have the wit to understand. In fact, Riesbeck's aims look far less unpretentious. For instance, his reading does not quite resolve the ambigui- ties in main Aristotelian terms like citizen, rule, and constitution, but rather it makes ?their presence less surprising than alternative accounts? (p. 228). According to Riesbeck, then, it would ?be foolish to claim that the view of Aristotle?s political philosophy? defended in this book ?is the only plausible, let alone possible, interpretation?. Riesbeck?s point, instead, is ?the more modest but still quite strong one that the texts, when taken together, are most plausibly read as read by him here (p. 288).In what follows I shall first (II) give an outline of the bountiful structure and content of this quite challenging book, only to focus upon just a couple of the many fascinating issues raised by this book: sharing in political rule (III, IV) and total kingship and the rule of law (V).